Advances in computing and data sciences : first International Conference, ICACDS 2016, Ghaziabad, India, November 11-12, 2016, Revised selected papers /: first International Conference, ICACDS 2016, Ghaziabad, India, November 11-12, 2016, Revised selected papers. (2017) - Unknown
No abstract available